Risiko Manajemen Operasional Pada Lembaga Pengelola Zakat di Surakarta - Rahma Yudi (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2021)
Zakat is a source of funds for the development of Islamic teachings. Zakat is a property that must be set aside by a Muslim or an institutional body owned by a Muslim in accordance with religious provisions to be given to people who are entitled to receive it. With good management, zakat is a potential fund that is used to promote general welfare for the whole community. Based on the inaugural meeting of the International Working Group on Zakat Core Principles (IWGZP) it was agreed that risk identification in zakat management is very important because it will affect the quality of zakat in the future. There are four types of identified risks and the zakat world must have a different concept clearly in mitigating these risks. First, reputational risk and lost muzakki. Second, distribution risk, third operational risk, and the fourth is the risk of transfer of zakat between countries.